Structural and Vibrational Characterization of the Chromophore Binding Site of Bacterial Phytochrome Agp11. (May 2017) - Takiden, Aref; Velazquez‐Escobar, Francisco; Dragelj, Jovan; Woelke, Anna Lena; Knapp, Ernst‐Walter; Piwowarski, Patrick; Bart, Franz; Hildebrandt, Peter; Mroginski, Maria Andrea
Abstract: Agp1 is a prototypical bacterial phytochrome from Agrobacterium fabrum harboring a biliverdin cofactor which reversibly photoconverts between a red‐light‐absorbing (Pr) and a far‐red‐light‐absorbing (Pfr) states. The reaction mechanism involves the isomerization of the bilin‐chromophore followed by large structural changes of the protein matrix that are coupled to protonation dynamics at the chromophore binding site. Histidines His250 and His280 participate in this process. Although the three‐dimensional structure of Agp1 has been solved at high resolution, the precise position of hydrogen atoms and protonation pattern in the chromophore binding pocket has not been investigated yet. Here, we present protonated structure models of Agp1 in the Pr state involving appropriately placed hydrogen atoms that were generated by hybrid quantum mechanics/molecular mechanics‐ and electrostatic calculations and validated against experimental structural‐ and spectroscopic data. Although the effect of histidine protonation on the vibrational spectra is weak, our results favor charge neutral H250 and H280 both protonated at N ε . However, a neutral H250 with a proton at N ε and a cationic H280 may also be possible. Furthermore, the present QM/MM calculations of IR and Raman spectra of Agp1 containing isotope‐labeled BV provide a detailed vibrational assignment of the biliverdin modes in the fingerprint region. Abstract : A combined computational/spectroscopic approach based on QM/MM‐ and electrostatic calculations and resonance Raman and IR spectroscopies was employed to generate a protonated structural model of the chromophore binding site of bacterial phytochrome Agp1. H250 and H280, involved in the photoinduced reaction mechanism, are most probably neutral charged and protonated at N ε, while a cationic H280 is also possible.